Prakiraan Suhu Rata-rata Berdasarkan Stasiun Deli Serdang Menggunakan Model Long Short-Term Memory - Ilham Junaedi; Endah Paramita; Nora Valencia Sinaga; Sri Wahyuni; Syahrul Humaidi (Yayasan Kita Menulis - JoCPES, 2021)
An understanding of designs and gage of typical temperature joined of parameter climate and climate data for better water resource organization and orchestrating amid a bowl is uncommonly imperative. Examine climate designs utilizing ordinary and neighborhood every year typical temperatures, compare and make discernments. amid this consider, we'll analyze adjacent and conventional typical temperature data in 96031 Station backed recognition station input. the preeminent objective of this considers to appear the execution of the conventional temperature in an exceedingly single station and to predict the ordinary temperature data utilizing the Long memory Illustrate approach. bolstered the comes about of standard informatics of exploring temperature with adjacent temperature relationship, we got the appear of preparing bend, remaining plot, and thus the diffuse plot is showed up utilizing these codes. the decent execution of 96031 Station had a Mean Squared Error esteem of 0.01 and R squared esteem 0.98, concerning zero will speak to superior quality of the indicator.